PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN DAN PENEKANAN TERHADAP SENJANGAN ANGGARAN DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI (Studi Empiris Pada OPD Kota Dumai - Agnes Teri Saptaria; Zulbahridar Zulbahridar; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The Purpose of this research is to examine : 1). The effect of budgetary participation on budgetary slack 2). The effect of budget goal clarity on budgetary slack 3). The effect of budget emphasis on budgetary slack 4). The effect of budgetary participation on budgetary slack with locus of control as moderating variable 5). The effect of budget goal clarity on budgetary slack with locus of control as moderating variable. 6). The effect of budget emphasis on budgetary slack with locus of control as moderating variable. The population on this study is Regional Working Units (OPD) at Dumai. This sample in this study was taken with a purposive sampling method. The sample in this study are performance of the district unit Dumai which amounted to 32 respondents. Data collections techniques used multiple regression analysis and moderating variable test analysis where processed using SPSS. The result of this study show that budgetary participation and budget emphasis significant influence on budgetary slack and then budget goal clarity doesn’t influence on budgetary slack. After that, variable locus of control moderate the effect of the budgetary participation, budget goal clarity and budget emphasis on budgetary slack. The amount of influence (????2) obtained at 0.618 or 61,8%. This means that 61,8% of budgetary slack by the value the independent variable, namely budget participation, budget goal clarity,budget emphasis and locus of control. While the remaining 31,2% is explained by other variables not examined in this study.Keywords: Participation, Clarity, Emphasis¸ Slack and Locus